Characterization of Changes in Subchondral Bone Tissue Density of the Ankle Joint in Taekwondo Players - Xu, Guanghua; Liu, Hongyu; Zhang, Lifu (Frontiers in Bioengineering and Biotechnology, 2022)
Background: It has been found that ankle joint impingement can cause articular cartilage injury, and the change of subchondral bone density and distribution under long-term stress loading can reflect the stress interaction of the articular surface and the difference in bone remodeling degree and predict the location of cartilage injury. Objective: To investigate the bone density distribution pattern of ankle joint subchondral bone under mechanical stress loading of Taekwondo, the volume proportion of bone tissue with different bone densities, and the distribution characteristics of bone remodeling position. Study design: A controlled laboratory study. Methods: Computed tomography data were collected from the feet of 10 normal subjects (control group) and 10 high-level Taekwondo athletes. First, the distribution pattern of the high-density area of the articular surface was determined by computed tomography osteoabsorptiometry and the nine-grid anatomical region localization method. Second, the percentage of bone volume (%BTV) and the distribution trend of bone tissue were measured. Result: In the present study, it was found that there were high-density areas in the 1st, 2nd, 3rd, 4th, 6th, 7th, and 9th regions of the distal tibia of Taekwondo athletes, and the distribution track was consistent with the high-density areas of the talar dome surface (1st, 2nd, 3rd, 4th, 6th, 7th, and 9th regions). In Taekwondo athletes, the percentage of bone tissue volume in the distal tibia and talus with high and moderate bone density was significantly higher than that in the control group (p < 0.05). Conclusion: The impact stress, ground reaction force, intra-articular stress, lower limb movement technology, lower limb muscle, and tendon stress caused by Taekwondo lead to special pressure distribution patterns and bone tissue remodeling in the ankle.